Penerapan Digital Marketing pada Komunitas Cimahi Kreatif Ekonomi Produktif di Cimahi - Rosmini Ramli; Esi Fitriani Komara; Rahardianto Rahardianto; Hariyadi Triwahyu Putra (Jurnal Inovasi Masyarakat, 2024)
The purpose of this service is to help business actors, especially MSMEs in the Cimahi Creative Productive Economy community, utilize digital technology in order to increase the volume and promotion of their sales so that the public as potential customers/consumers can access and find out the details of the products or services offered. The problem of these MSMEs is that they still have limited ability and understanding in the use of digital technology to market the products or services created so that they experience obstacles in increasing sales and it is even difficult to introduce their products due to shifts in consumer behavior in purchasing consumer goods due to increasingly rapid technological developments. The method that will be used in solving the problem is to conduct a process of training and mentoring in the application of digital marketing so that it can have a direct impact on MSME actors. The results show that after the training process and continued with mentoring, the average business actor has been able to use digital marketing in his business, but there are still some who have not due to other obstacles such as devices and other technicalities.